Resource Efficient For Hybrid Fiber-Wireless Communications Links In Access Networks With Multi Response Optimization Algorithm - Wong, Adam Yoon Khang; Indra, Win Adiyansyah; Jamil Alsayaydeh, Jamil Abedalrahim; Mohamat Gani, Johar Akbar; M. Idrus, Sevia; Pusppanathan, Jaysuman (Asian Research Publishing Network, 2021)
Mobile Ad-hoc Network (MANET) is currently popular at demand as a solution in numerous deployments that cover from the combat zone to the user’s parlor due to its quickly deployable with adaptive topology and able to function without any infrastructure. However, variable topology is one of the key challenges since the network throughput and energy consumption depends on number of possible connections. This work proposes a Multi response Optimization (MO) algorithm, named MO-LMMHOWAN that apply in Last Mile Mobile Hybrid Optical Wireless Access Network (LMMHOWAN). In this perspective, the paper originally proposes a model and an architecture that roughly combine MANET and FiWi domains based on adaptive data rate transmission of cross layer scheme integrated with Taguchi method: the primary idea is that this MANET and FiWi can route the packet in accordance to the pre-optimized and robust profile drive by the adaptive data rate, thus mutually enhancing their capability of packet transmission over hybrid FiWi- MANET networks. Technically, the effects of seven controlled factors and two uncontrolled factors were investigated by implementing the Orthogonal Arrays (OA) of Taguchi experimental method on a AODVUU routing path in last mile mobile HOWAN. The study here is established on energy consumption, Packet Delivery Ratio (PDR) and throughput metric with varying nodes scenario. This result is compared to the (non-Taguchi) work study which further reduces the variability among routing configuration parameters and shows superior performance improvement with regards to capacity, energy consumption and PDR with values of 77.89%, 33.76%, and 25.44%, respectively.